House of frozen / Natasah Sudin, Ain Nadiah Ahmad and Hazirah Azami - Sudin, Natasah; Ahmad, Ain Nadiah; Azami, Hazirah (2018)
This study will study about frozen food and this company is doing online business in Facebook and WhatsApp. The company name is house of frozen. This company produce frozen food like curry puff, "cucur badak", "keria", and sandwich sardine. The problem of this company is unable to reply on time and its will take more than 24 hours to reply the customer. In this case study, we will evaluate the delivery system of this company.